Diagnosis and Treatment of Infantile Hemangioma from the Primary Care Paediatricians to the Specialist: A Narrative Review - Francesco Bellinato; Maria Marocchi; Luca Pecoraro; Marco Zaffanello; Micol Del Giglio; Giampiero Girolomoni; Giorgio Piacentini; Erika Rigotti (MDPI AG, 2024)
Infantile haemangiomas (IHs) affect 3-10% of infants, 10% of whom need topical or systemic beta-blocker therapy. Propranolol is the first choice for IHs with a high risk of complications. Since more than half of IHs leave a permanent mark, to reduce outcomes, it is essential to start oral propranolol (2-3 mg/kg/day in 2 doses/day) within the 5th month of life (i.e., during the proliferative phase) and to complete the therapy cycle for at least 6 months. This review aims to summarise the epidemiology, clinical presentation, diagnosis, and treatment of IHs and to highlight the importance of proper referral to specialised hub centres. Patients with vascular anomalies, particularly those suspected of having IH, should be referred to a specialised centre for accurate diagnosis, management by a multidisciplinary team, and timely treatment. IHs may pose life-threatening, functional, and aesthetic risks or may ulcerate. Segmental infantile haemangioma of the face/neck and the lumbosacral regions can be associated with various malformations. To ensure timely specialist evaluation and treatment to reduce the potential risk of complications, it is essential to identify high-risk IHs rapidly. The Infantile Haemangioma Referral Score (IHReS) scale is an important tool to assist primary care paediatricians and general dermatologists.